WDM-PON architecture with centralized generation of optical multi-carriers - Silva, Rui Miguel Horta Coelho da (2014)
The rapid growth of the telecommunications area and the increasing demand for bandwidth by users has led to the need of develop the Wavelength-division multiplexed passive optical network (WDM-PON) architecture, which can increase the bandwidth of the existing network without the necessity of installing new fiber . A key technique for the high capacity WDM-PON networks is the generation of optical multi-carriers. This technique is the main focus point of this dissertation, which begins to look at the generation of optical multi-carriers in a general way and then will try to find the best way to apply this technique to an Ultra Dense WDM-PON (UDWDM-PON) application. Two distinct methods of generating optical multi-carriers were tested and it was concluded that the ‘single stage dual arm driven MZM’ is the one that offers more benefits to an UDWDM-PON application.